2020
DOI: 10.1101/2020.11.09.20228718
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Public participation in crisis policymaking. How 30,000 Dutch citizens advised their government on relaxing COVID-19 lockdown measures

Abstract: Following the outbreak of COVID-19, governments took unprecedented measures to curb the spread of the virus. Public participation in decisions regarding (the relaxation of) these measures has been notably absent, despite being recommended in the literature. Here, as one of the exceptions, we report the results of 30,000 citizens advising the government on eight different possibilities for relaxing lockdown measures in the Netherlands. By making use of the novel method Participatory Value Evaluation (PVE), part… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…A Dutch language report of our study was cited in the long term COVID-19 strategy of the Dutch government" (Mouter et al 2022) [p. 4] In the other two studies, the description was either vague or limited. Mouter et al (2020) stated that "We do not know whether and how our results affected political decisions on the relaxation of lockdown measures, but it is noteworthy that the Dutch government decided on 6 May to start with the relaxation of lockdown measures for contact professions which was in line with our result that reopening contact professions would have broad support in society" (Mouter, Hernandez, and Itten 2020) [p. 28].…”
Section: Analysis Of Included Studies (N = 3)mentioning
confidence: 56%
See 1 more Smart Citation
“…A Dutch language report of our study was cited in the long term COVID-19 strategy of the Dutch government" (Mouter et al 2022) [p. 4] In the other two studies, the description was either vague or limited. Mouter et al (2020) stated that "We do not know whether and how our results affected political decisions on the relaxation of lockdown measures, but it is noteworthy that the Dutch government decided on 6 May to start with the relaxation of lockdown measures for contact professions which was in line with our result that reopening contact professions would have broad support in society" (Mouter, Hernandez, and Itten 2020) [p. 28].…”
Section: Analysis Of Included Studies (N = 3)mentioning
confidence: 56%
“…• a large-scale survey from the same research team gathering public views and preferences regarding eight policy options for relaxing lockdown measures in the Netherlands (n = 29,358); (Mouter, Hernandez, and Itten 2020) (Mouter 2020); and • examination of over 150,000 data rows from the Chinese social media platform Weibo with a focus on transport / lockdown policies. (Zha et al 2023) All studies reported that their approaches were generally effective and acceptable for the purpose of gathering POD to inform policymaking.…”
Section: Analysis Of Included Studies (N = 3)mentioning
confidence: 99%
“…Preferences of citizens on pandemic management were gauged, and information about consequences of their theoretical decisions was provided. 68 …”
Section: Discussionmentioning
confidence: 99%
“…Based on the above considerations, we argue that a more inclusive conception of science is one in which experts in action make decisions based not just on epistemic soundness or efficiency but also consider the needs of communities that are larger than that of the experts themselves. These experts, in our view, should therefore be aware of the diversity of interests at stake and consider the possibility of having sometimes a non-univocal and objective evaluation of complex situations (Mouter et al 2020). This, in our view, does not mean devaluing science or reducing its role in society but rather quite the opposite.…”
Section: The Challenge Of Inclusivenessmentioning
confidence: 96%